2019
DOI: 10.1590/0100-29452019004
|View full text |Cite
|
Sign up to set email alerts
|

Advances in fruit crop propagation in Brazil and worldwide-apple trees

Abstract: Apple production has been an important economic activity worldwide. The wide dissemination and cultivation of apple trees in several regions of the world is due to the development of propagation techniques from its domestication to the present time. Apple trees can be propagated by seeds, restricted to the use in breeding programs, and multiplied by several methods of vegetative propagation, both for rootstocks and apple scion cultivars. Considering the high technological level currently used in apple crop man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…One of the most important characteristics of a rootstock is its compatibility with the main cultivated varieties. The main properties of fruit trees depend on the quality of the obtained planting material: winter hardiness, vigor, precocity, productivity, fruit quality [13][14][15]. To determine the compatibility of the clonal rootstocks and the main varieties of apple trees used in the horticulture of the region, a series of experiments on different combinations of scions and rootstocks was carried out in the nursery:…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important characteristics of a rootstock is its compatibility with the main cultivated varieties. The main properties of fruit trees depend on the quality of the obtained planting material: winter hardiness, vigor, precocity, productivity, fruit quality [13][14][15]. To determine the compatibility of the clonal rootstocks and the main varieties of apple trees used in the horticulture of the region, a series of experiments on different combinations of scions and rootstocks was carried out in the nursery:…”
Section: Resultsmentioning
confidence: 99%
“…However, areas with a predominance of slopes require adequate management due to infiltration with low drainage capacity, accentuated by the frequency of rain. Moreover, for Petri et al (2019) and Bauer et al (2020), the symptoms of diseases and disorders prevalent in apple orchards are frequent in shady and humid places, influenced by low temperatures and reduced levels of light.…”
Section: Characterization Of Orchards According To Reliefmentioning
confidence: 99%
“…Synthetic cytokinins have a remarkable ability to stimulate growth in tissue culture and, more recently, organs in the entire plant system. Petri et al [14] also observed that the application of TDZ and aminoethoxyvinylglycine (AVG) increase the fruit set in cultivars Monalisa and Maxi Gala.…”
Section: Introductionmentioning
confidence: 97%